Lipedema stage affects adipocyte hypertrophy, subcutaneous adipose tissue inflammation and interstitial fibrosis - Kruppa, Philipp; Gohlke, Sabrina; Łapiński, Kamila; Garcia-Carrizo, Francisco; Soultoukis, George A.; Infanger, Manfred; Schulz, Tim J.; Ghods, Mojtaba (Frontiers in Immunology, 2023)
Lipedema is a painful subcutaneous adipose tissue (SAT) disease characterized by adipocyte hypertrophy, immune cell recruitment, and fibrosis in the affected areas. These features are thought to contribute to the development and progression of the condition. However, the relationship between lipedema disease stage and the associated adipose tissue changes has not been determined so far.SAT biopsies of 32 lipedema patients, ranging across the pathological stages I to III, and 14 BMIand age-matched controls were harvested from lipedema-affected thighs and non-symptomatic lower abdominal regions. Histological and immunohistochemical (IHC) staining and expression analysis of markers for adipogenesis, immunomodulation, and fibrosis were performed on the tissue biopsies.Lipedema patients showed increased adipocyte areas and a stage-dependent shift towards larger cell sizes in the thighs. Lipedema SAT was linked with increased interstitial collagen accumulation in the thighs, but not the lower abdominal region when compared to controls. There was a trend toward progressive SAT fibrosis of the affected thighs with increasing lipedema stage. Elevated gene expression levels of macrophage markers were found for thigh SAT biopsies, but not in the abdominal region. IHC staining of lipedema thigh biopsies confirmed a transiently elevated macrophage polarization towards an M2-like (anti-inflammatory) phenotype.In summary, lipedema SAT is associated with stage-dependent adipocyte hypertrophy, stageprogressive interstitial fibrosis and elevated proportion of M2-like macrophages. The character of the inflammatory response differs from primary obesity and may possess an essential role in the development of lipedema.